Sensory and nutritional effects of citrus and pineapple enrichment in yogurt production - Boev Sergey; Trubnikov Vladimir; Grashkov Sergei; Eskov Dmitry (E3S Web of Conferences)
This paper explores the potential applications of pineapple and orange in yogurt production, examining their addition in various ratios and their impact on quality indicators. The study analyzed samples of enriched yogurt. Pineapple and orange enrichments were added in different proportions ranging from 2:1 to 3:1, meaning three parts pineapple and one part orange relative to the mass of the produced yogurt. To evaluate the obtained samples, researchers conducted organoleptic and other analyses. The results demonstrated that the addition of these components increased ash content and iron levels compared to the control sample. The highest concentration of the studied element was achieved with the addition of 15% pineapple and 5% orange. Based on the experimental results, it can be concluded that incorporating fruit components into the yogurt recipe increases ash content and, consequently, the elemental composition, as confirmed by the conducted studies. In terms of organoleptic properties, the best sample was the one with fruit components added in a 3:1 ratio (three parts pineapple and one part orange). This ratio proved optimal for enrichment in yogurt production.